The effect of female breast surface area on cutaneous thermal sensation, wetness perception and epidermal properties - Hannah Blount; Alessandro Valenza; Jade Ward; Silvia Caggiari; Peter R. Worsley; Davide Filingeri (Experimental Physiology)
Abstract Female development includes significant size changes across the breast. Yet, whether differences in breast surface area (BrSA) modify breast sensitivity to warm, cold and wetness, and the associated epidermal properties (skin thickness and surface roughness) remain unclear. We investigated the relationship between BrSA and thermal and wetness perception, as well as epidermal properties, in 21 females (28±10 years) of varying breast sizes (BrSA range: 147–502 cm2), at multiple breast sites (i.e., nipple, above and below the nipple, and bra triangle). Associations between BrSA and the perceptual and epidermal variables were determined via correlation analyses. Differences across test sites were assessed by repeated‐measures ANOVA. Our results did not support the hypothesis that larger breasts present reduced thermal and wetness sensitivity, except for the above nipple site, which presented reduced warm sensitivity with increasing BrSA (r = −0.61, P = 0.003). We also found a heterogeneous distribution of cold, but not warm or wetness, sensitivity across the breast, with the above nipple site presenting lower cold sensitivity than any other site (P < 0.015). Our findings did not indicate any association between BrSA and epidermal properties (thickness and roughness), nor any site‐dependent variation in these anatomical parameters (P > 0.15). We conclude that, while some skin‐site (i.e., above the nipple) and perceptual modality‐dependent (i.e., warm sensitivity) differences were observed, BrSA‐dependent variations in thermal and wetness sensitivity were not a generalised feature of the skin covering the breast. These observations advance our fundamental understanding of breast sensory function, and they could inform the design of user‐centred clothing such as bras.